Peri-Urban and Informality in Teluknaga, Tangerang Regency, Indonesia - Hadi, Cipta; Ellisa, Evawani (CSID Journal of Infrastructure Development, 2021)
‘Desakota’ has been acknowledged as a unique landscape condition in South East Asia and Indonesia especially. In the middle of emerging economies and rapid urban development, ‘desakota’ as a peri-urban area suffers environmental degradation in the economy and socio-culture because of poor planning and control from state and local authority. Inequality, spatial segregation, and inadequate infrastructure or slums are issues that peri-urban’desakota’ has to encounter. Nevertheless, as a tool for producing and adapting the built environment and introducing a spatial order, urban design shows less concern for developing this distinct peri-urban area. This study conducted in Teluknaga, Tangerang, the neighboring Jakarta, examined the significance of informality which shapes a compact urban form in the 'desakota' area. Data collection of the study was done through field study by conducting interviews, observations, and direct mapping. We conclude that the informality potents should be considered for designing ‘desakota’ to maintain its compact form and create a more sustainable urban form and a better urban life.